Implementasi Model Pembelajaran PBL dalam Meningkatkan Hasil Belajar Peserta Didik Kelas 4 pada Mata Pelajaran IPS Materi “Indonesia Kaya Budaya” SD N 2 brangkal. - Nova Sugiana Purwaningrum; Selvia Maharani; Isna Rahmawati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Learning models are important in teaching and learning activities. Implementing the Problem Based Learning (PBL) learning model or problem-solving learning model is one way for educators to attract enthusiastic students to have more fun learning and understand the material. Including science and technology material using the PBL model is an effort by educators at SDN 2 Brangkal to be able to convey material that follows the Merdeka curriculum well. We conducted this research to improve the learning outcomes of grade 4 students at SDN 2 Brangkal using the PBL learning model in the science material Chapter 6 "Indonesia is Rich in Culture". The method we use in this research is descriptive qualitative through observation or class observations and documentation. So we can conclude that teaching and learning activities using the PBL model can attract students' enthusiasm for learning. And get maximum learning results. As an educator, choosing learning models and strategies is very necessary to support students' success in achieving a goal.